1997
DOI: 10.1002/(sici)1097-0223(199707)17:7<607::aid-pd118>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 12 assays for detecting hCG and related molecules in urine samples from Down syndrome pregnancies

Abstract: Urine is a new medium for Down syndrome testing. In an effort to determine the best type of human chorionic gonadotropin (hCG)‐related immunoassay for urine testing, we examined 14 Down syndrome and 91 unaffected pregnancy urine samples with 12 established assays. The assays included (a) those that detect hCG β‐core fragment only; (b) those that detect β‐core fragment with less than 18 per cent free β‐subunit cross‐reactivity; (c) that which equally detects free β‐subunit and β‐core fragment; and (d) those tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…This is consistent with Spencer et al (1996) who found that the detection efficiency of urinary free beta (hCG) was greater than that of beta-core (hCG), and Hayashi et al (1996) who found a higher MoM with urinary free beta (hCG) than urinary beta-core (hCG) in two out of three Down syndrome cases. The result, however, contrasts with Cole et al (1997), who found that detection efficiency was greater with beta-core (hCG) than free beta (hCG) in a set of 14 Down syndrome cases. The Cole et al study may be biased, however, since this data set was previously known to have an extremely high beta-core (hCG) Down syndrome MoM prior to evaluating free beta (hCG).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This is consistent with Spencer et al (1996) who found that the detection efficiency of urinary free beta (hCG) was greater than that of beta-core (hCG), and Hayashi et al (1996) who found a higher MoM with urinary free beta (hCG) than urinary beta-core (hCG) in two out of three Down syndrome cases. The result, however, contrasts with Cole et al (1997), who found that detection efficiency was greater with beta-core (hCG) than free beta (hCG) in a set of 14 Down syndrome cases. The Cole et al study may be biased, however, since this data set was previously known to have an extremely high beta-core (hCG) Down syndrome MoM prior to evaluating free beta (hCG).…”
Section: Discussioncontrasting
confidence: 70%
“…However, using the distributional parameters for beta-core (hCG) presented in their study (median: 0·0; SD (Log 10 ): 0·368), the 95th percentile would be 4·03 MoM, indicating that only 7/13 (54 per cent) cases were above the 95th percentile. Regardless, reported results (median Down syndrome MoM 4·1, detection efficiency 62 per cent) from this prospective study were less favourable than those seen with the three earlier data sets (Canick et al, 1995Cole et al, 1997;Cuckle et al, 1994Cuckle et al, , 1995. Cole and colleagues have focused on assay methods to explain discrepancies in median Down syndrome MoM results among studies (Cole, 1995(Cole, , 1997.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Six of these papers (Cuckle et al, 1994(Cuckle et al, , 1995Canick et al, 1995;Cole et al, 1997a;Kellner et al, 1996;Fig. 2-Total oestriol levels in urine samples from 492 second-trimester pregnancies, 12 Down syndrome cases (), and 480 controls (v). Concentrations are normalized to creatinine (ng total oestriol/mg creatinine).…”
Section: Discussionmentioning
confidence: 99%
“…Urine samples were initially diluted 1 to 31 for immunoassay. Further dilutions, 1 to 1, 1 to Cuckle et al (1994) -Core fragment 67 7 >80 (5) Cuckle et al (1995) -Core fragment 294 24 80 (5) Canick et al (1995) -Core fragment 91 14 88 (5) Spencer et al (1996) -Core fragment 400 29 41 (5) Kellner et al (1996) -Core fragment 206 32 72 (5) Isozaki et al (1997) -Core fragment 709 13 62 (5) Cole et al (1997a) -Core fragment 91 14 93 (10) Hyashi and Kozu (1995) Free with -core 150 5 20 (5) Spencer et al (1996) Free -subunit 400 29 58 (5) Cole et al (1997a) Free -subunit 91 14 47 (10) Cole et al (1997b) Free -subunit 709 13 54 (5) Cole et al (1997c) hCG only 91 14 43 (10) Cole et al (1997a) hCG with free 91 14 50 (10) Kellner et al (1996) Total oestriol 206 32 22 (5) Cuckle et al (1995) Total oestrogens 294 24 34 (5) Spencer et al (1992) Free -subunit 2400 90 54 (5) Ryall et al (1992) Free -subunit 1400 57 47 (5) Wald et al (1993) Free -subunit 367 75 55 (5) Spencer et al (1992) hCG with free 2400 90 48 (5) Ryall et al (1992) hCG with free 1400 57 42 (5) Wald et al (1993) hCG 10, and 1 to 100, were made as needed. The total oestriol levels (ng/ml) were also normalized to adjust for variations in the urine concentration by dividing by the creatinine concentration (mg/ml).…”
Section: Methodsmentioning
confidence: 99%